Strategic Formulation for Accelerated Fast Track Programs : A Case Study Using SWOT – AHP at Universitas Brawijaya - Fahmi Syafikah Putri; Bambang Supriyono; Ike Wanusmawatie (STAI Hubbulwathan Duri, 2025)
Indonesia faces a low number of master’s graduates, partly due to implementation challenges in programs like the Fast Track at Universitas Brawijaya’s Faculty of Administrative Sciences. This research aims to evaluate the Fast Track program using SWOT (Strengths, Weaknesses, Opportunities, Threats) analysis and develop strategic plans using the Analytical Hierarchy Process (AHP). A mixed methods approach with a dominant-less dominant design was employed. Data were gathered through interviews with two Fast Track students, three master’s program heads, and the vice dean of academics. Thirteen Fast Track students completed questionnaires. Additionally, direct observations were conducted, and relevant university regulations were reviewed. Data analysis included interactive analysis, SWOT analysis, and AHP to formulate short-, medium-, and long-term strategies. Findings indicate that internal strengths are the primary drivers for program success. Short-term strategies should prioritize improving students’ time management and academic readiness. Medium-term strategies must focus on aligning thesis topics with suitable supervisors to facilitate academic progress. Long-term strategies should involve consistent monitoring and evaluation to ensure students complete the program within the designated five years. Strategic improvement relies on enhancing coordination between undergraduate and master’s programs. This alignment is essential not only for academic success but also for supporting students' mental well-being throughout the accelerated track.